Method of ISSR-marking in the study of genetic diversity of flax varieties - T. A. Bazanov; I. V. Ushapovsky; N. N. Loginova; E. V. Smirnova; P. D. Mikhaylova (Аграрная наука Евро-Северо-Востока)
The genetic diversity of crop varieties should be assessed using modern molecular markers. One of the most promising and simple methods of plant genetic analysis is intermicrosatellite labeling (ISSR). The purpose of this research is to study the polymorphism of varieties of fiber flax and linseed flax included in the State Register of Breeding Achievements of the Russian Federation, as well as local forms of fiber flax using ISSR markers. The objects for the research were 83 samples from the collection of the Federal Research Center for Bast Fiber Crops, among them 24 varieties of linseed flax, 56 varieties of fiber flax of domestic and foreign breeding, and three local forms from the Central Non-Black Earth Region. Genetic analysis was carried out by PCR method using a set of 25 ISSR primers. Detection of amplification products was carried out using electrophoresis in 1.5% agarose gel. Based on intraspecific selection of flax varieties to oilseed and fiber forms, a cluster analysis was performed according to the results of ISSR labeling independently in each of two groups that allowed to increase the reliability of conclusions on the existing dependences. Dendrograms of the genetic similarity of the studied samples of linseed flax and fiber flax were studied independently from each other. As a result of the analysis, linseed flax varieties were divided into five clusters, which made it possible to establish dependencies related to their origin (originator of the variety) and oil content in the seed. The dendrogram which included varieties of fiber flax and its local forms, revealed twelve subclusters forming three uneven groups. Almost every group had its own characteristic feature, not related to the geography of origin. The grouping of varieties occurred mainly on the basis of their various characteristics in terms of flax fiber content, ripening time and resistance to environmental stress factors. The results of the research show the applicability of using the ISSR-markers as a valid and accessible method for developing the elements of marker-associative breeding of bast fiber crops.